A Single Center Experience with Post Transplant Tuberculosis in a Developing Country. (July 2018) - Kenwar, Deepesh; Singh, Sarbpreet; Sharma, Ashish; Singh, Navdeep; Kapoor, Kunal
Abstract : Background: Tuberculosis (TB) is endemic in India. Our transplant center performs over 250 renal transplants a year and TB is a significant morbidity in the post transplant period. This retrospective review of follow up data provides an idea of the disease burden and its treatment in the post transplant population at our center. Methods: A retrospective review of follow up data from Jan 2004 to Dec 2016 was undertaken to identify those patients who either tested positive for acid fast bacilli (AFB) or were treated with anti tubercular therapy (ATT) for at least 6 months were identified and details of their presentation, immunusuppression and ATT were noted. Additional information on associated infections and outcomes were also noted. Results: Out of data reveiwed for 2600 patients 89 (M:F 75:14) fulfilled our criteria for identifying patients with TB. The mean age at presentation was 35.21 +- 9.78 yrs and the mean time post transplant was 25.58 +- 32.32 months. Sixteen patients had received induction immunosuppression with anti-thymocyte globulin (n=8), belatacept (n=1), basiliximab (n=6) or dacluzimab (n=1). Fifty eight patients had received ATT with a fluoroquinolone substituting rifampicin for financial contraints and 10 patients had taken rifampicin based ATT while ATT data was unavailable for 21 patients. Patients were either on tacrolimus (n=67) cyclosprin (n=15) or sirolimus (n=1) in combination with either azathioprine (n=10) or mycophenolate (n=68). Associated infections were UTI (n=10), bacterial pneumonias (n=6), cancidiasis (n=5), aspergillosis (n=1), herpesviridae infections (n=7) and viral hepatitis (n=14). There were only two deaths due to tuberculosis out of 55 deaths directly attributable to infections in the follow up group. Conclusion: Tuberculosis is a significant disease in the post transplant population in developing nations and treatment with non rifampicin based ATT should be studied and its role defined.